The complete mitochondrial genome of a threatened loach (Beaufortia kweichowensis) and its phylogeny - Zheng-Yong Wen; Bi-Wen Xie; Chuan-Jie Qin; Jun Wang; Deng-Yue Yuan; Rui Li; Yuan-Chao Zou (Conservation Genetics Resources, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

Holocene activity evidence on the southeast boundary fault of Heqing basin, middle segment of Heqing-Eryuan fault zone, West Yunnan Province, China - Chang-bin Sun; De-wen Li; Xiao-ming Shen; Yan-rui Kang; Rui Liu; Ya-jiao Zhang (Journal of Mountain Science, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Waterlogging risk assessment based on self-organizing map (SOM) artificial neural networks: a case study of an urban storm in Beijing - Wen-li Lai; Hong-rui Wang; Cheng Wang; Jie Zhang; Yong Zhao (Journal of Mountain Science, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

The transgenic expression of human follistatin-344 increases skeletal muscle mass in pigs - Fei Chang; Rui Fang; Meng Wang; Xin Zhao; Wen Chang; Zaihu Zhang; Ning Li; Qingyong Meng (Transgenic Research, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Paenibacillus oryzisoli sp. nov., isolated from the rhizosphere of rice - Jun Zhang; Xiao-Tong Ma; Jun-Sheng Gao; Cai-Wen Zhang; Juan-Juan Zhao; Rui-Jie Zhang; Li-An Ma; Xiao-Xia Zhang (Antonie van Leeuwenhoek, 2017)